Analysis of HCV quasispecies dynamic under selective pressure of combined therapy - Jardim, Ana C.G. [UNESP]; Bittar, Cíntia [UNESP]; Matos, Renata P.A. [UNESP]; Yamasaki, Lílian H.T. [UNESP]; Silva, Rafael A.; Pinho, João R.R.; Fachini, Roberta M.; Carareto, Claudia M.A. [UNESP]; de Carvalho-Mello, Isabel M.V.G.; Rahal, Paula [UNESP] (Springer Nature, 2013)
Background: The quasispecies composition of Hepatitis C virus (HCV) could have important implications with regard to viral persistence and response to interferon-based therapy. The complete NS5A was analyzed to evaluate whether the composition of NS5A quasispecies of HCV 1a/1b is related to responsiveness to combined interferon pegylated (PEG-IFN) and ribavirin therapy.Methods: Viral RNA was isolated from serum samples collected before, during and after treatment from virological sustained responder (SVR), non-responder (NR) and the end-of-treatment responder patients (ETR). NS5A region was amplified, cloned and sequenced. Six hundred and ninety full-length NS5A sequences were analyzed.Results: This study provides evidence that lower nucleotide diversity of the NS5A region pre-therapy is associated with viral clearance. Analysis of samples of NRs and the ETRs time points showed that genetic diversity of populations tend to decrease over time. Post-therapy population of ETRs presented higher genetic distance from baseline probably due to the bottleneck phenomenon observed for those patients in the end of treatment. The viral effective population of those patients also showed a strong decrease after therapy. Otherwise, NRs demonstrated a continuous variation or stability of effective populations and genetic diversity over time that did not seem to be related to therapy. Phylogenetic relationships concerning complete NS5A sequences obtained from patients did not demonstrate clustering associated with specific response patterns. However, distinctive clustering of pre/post-therapy sequences was observed. In addition, the evolution of quasispecies over time was subjected to purifying or relaxed purifying selection. Codons 157 (P03), 182 and 440 (P42), 62 and 404 (P44) were found to be under positive selective pressure but it failed to be related to the therapy.Conclusion: These results confirm the hypothesis that a relationship exists between NS5A heterogeneity and response to therapy in patients infected with chronic hepatitis C. © 2013 Jardim et al.; licensee BioMed Central Ltd.
Keywords: nonstructural protein 5A; peginterferon alpha2b; ribavirin; adult; amino acid sequence; amino terminal sequence; bottleneck population; carboxy terminal sequence; cladistics; clinical effectiveness; codon; combination chemotherapy; drug response; female; genetic distance; genetic variability; hepatitis C; Hepatitis C virus; human; major clinical study; male; molecular phylogeny; nonhuman; nonsense mutation; nucleotide sequence; phylogenetic tree; purifying selection; sequence alignment; sequence analysis; sex difference; viral clearance; viremia; virus load